A reflection on the use of digital whiteboards: transforming classroom learning among medical students - Azme, Nasibah (2024)
Finding ways to engage students and improve their learning is of utmost importance in the field of education. Significant technological tools that are used nowadays by many educators in this regard include digital whiteboards (David & Weistein, 2023; Tan et al., 2015). This critical technological tool offers a wide range of features that support and expand teaching methods in typical classroom settings. The use of digital whiteboards is associated with a more dynamic and interesting classroom setting, which according to research leads to a better overall learning experience. According to several studies, incorporating this technology into teaching methods not only diversifies teaching approaches but also enhances student performance (Luo et al., 2023; Hendawi & Nosair, 2020; Dudaitė & Prakapas, 2019).